1998
DOI: 10.1111/j.1447-0756.1998.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences of IgG and IgM Antibodies to Phospholipids and APTT among Non‐Pregnant and Pregnant Women

Abstract: Standard criteria for the positivity of the IgG antibody to CL and PS and the prolongation of APTT in pregnancy should employ the values of normal pregnant women rather than those of non-pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Since the hypercoagulable state of pregnancy is so well described [5, 10, 11, 15–17, 21], we were surprised to find few papers on reference ranges for haematology tests in pregnancy [7, 22, 23], although data do exist for other standard laboratory tests in pregnancy [21, 24–26]. It is reassuring that the current study has demonstrated broadly similar reference ranges for PT and APTT in pregnancy compared with the laboratory ranges, but our finding of higher fibrinogen levels in pregnancy should be considered when interpreting standard coagulation tests in the peripartum period.…”
Section: Discussionsupporting
confidence: 52%
“…Since the hypercoagulable state of pregnancy is so well described [5, 10, 11, 15–17, 21], we were surprised to find few papers on reference ranges for haematology tests in pregnancy [7, 22, 23], although data do exist for other standard laboratory tests in pregnancy [21, 24–26]. It is reassuring that the current study has demonstrated broadly similar reference ranges for PT and APTT in pregnancy compared with the laboratory ranges, but our finding of higher fibrinogen levels in pregnancy should be considered when interpreting standard coagulation tests in the peripartum period.…”
Section: Discussionsupporting
confidence: 52%